Energy Potential and Impact of Briquettes Produced from Soy Sauce Industry Soybean Waste and Sugarcane Bagasse - Claudya, Agnes Lidya; Farahdiba, Aulia Ulfah; Yayok Suryo Purnomo (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Indonesia's energy demand continues to increase, but energy fulfillment still relies on coal, which has a negative impact on the environment. Seeing the potential of biomass as fuel, this study is intended to analyze the potential use of soybean dregs from soy sauce factories and sugarcane bagasse as fuel and to evaluate the characteristics of biomass briquettes according to the composition and particle size of the materials. Sugarcane bagasse and soy sauce bagasse were varied with a ratio of 63%:27%, 45%:45%, and 27%:63%, respectively with a mixture of 10% adhesive from cassava flour and molasses. The mesh size was chosen at 80 (177 μm) and 150 (99 μm) to compare the effect of particles <100 μm and >100 μm. Briquettes with characteristics that meet almost all aspect standards are briquettes with a composition of 27% soy sauce dregs and 63% sugarcane dregs with a mesh size of 150. The results of the water content are 4.20%, ash content 7.46%, volatile matter content 23.73%, and calorific value 5948 calories/gram. However, the results of the CO emission test in the early minutes of combustion (1287 ppm) did not meet the quality standard. This study proves that soy sauce dregs and sugarcane dregs waste can be an environmentally friendly alternative fuel with further emission control.